Awake Flexible Fiberoptic Laryngoscopy to diagnose glossoptosis in Robin Sequence patients. (9th February 2016) - Basart, H.; König, A.M.; Bretschneider, J.H.; Hoekstra, C.E.L.; Oomen, K.P.Q.; Pullens, B.; Rinkel, R.N.P.M.; van Gogh, C.D.L.; van der Horst, C.M.A.M.; Hennekam, R.C.
Abstract : Background: Robin Sequence (RS) is usually defined as the combination of micrognathia, glossoptosis and upper airway obstruction. No objective criteria to diagnose RS exist. To compare management strategy results, a single RS definition using objective criteria is needed. The most frequently used primary diagnostic tool for glossoptosis is awake Flexible Fiberoptic Laryngoscopy (aFFL). Objectives: To determine the reliability of the aFFL videos as an independent diagnostic tool itself, rather than on the complete evaluation of a patient. Design, setting, participants: All RS individuals from an existing cohort with an available aFFL video were included retrospectively. Thirty age‐matched patients without pathologic findings on aFFL were used as controls. aFFL videos were scored by six otolaryngologists as: a. Marked glossoptosis, b. Mild glossoptosis, c. Severity unknown, d. No glossoptosis, e. Insufficient video quality. Videos were anonymised and rated twice, in altered sequences, after a washout period of minimally 2 weeks. Main outcome measures: Inter‐rater and intrarater agreement. Results: Twenty‐six videos of 16 RS patients and 30 videos of controls were included. Inter‐rater agreement was fair in the whole group ( κ : 0.320) and RS group ( κ : 0.226), and fair to moderate in determining presence of glossoptosis (total group κ : 0.430; RS κ : 0.302; controls κ : 0.212). The intrarater agreement for the presence of glossoptosis in RS was moderate ( κ : 0.541). Conclusions: aFFL offers fair to moderate inter‐rater agreement, with moderate intrarater agreement, in evaluating glossoptosis in RS. Using aFFL as the single tool in choosing management strategies in RS seems insufficient. There is need for a more reliable, patient friendly diagnostic tool or an internationally accepted aFFL scoring system, to diagnose glossoptosis in RS.